Impacts of metal-based engineered nanomaterials on soil communities. Issue 3 (11th May 2016) - McKee, Moira S.; Filser, Juliane
Abstract : A comprehensive review of the effects of metal-based nanoparticles on trophic groups, interactions, ecosystem functions and biodiversity of soil communities. Abstract : As use and emission of metal-based engineered nanomaterials (MENM) is steadily increasing, concern of adverse effects on soil communities is rising. MENM are not only toxic to various organisms in soil, but can bioaccumulate, trophically transfer and even biomagnify in some systems. Negative effects of MENM on plant-fungi and plant-bacteria interactions have been shown in various studies, while further research on other forms of interactions ( e.g. competition, predation) is needed to assess potential risks. Negative effects of MENM on nitrogen turnover and increased carbon emissions have been shown in numerous studies, and other biogeochemical cycles potentially at risk are addressed here. Most data to date has been collected on the consequences of MENM exposure for microorganisms and particle dependent changes in their community composition have been shown; data on other organism communities is however not available. In this review we summarize community interactions and soil ecosystem processes affected by MENM exposure and show how soil organisms influence MENM properties. Based on short- and long-term toxic effects, multiple inter- and intraspecific interactions and chemical processes we develop a conceptual framework. We postulate that cascading and potentially catalytic effects of MENM in soil might explain toxic effects at low concentration after longer exposure. Therefore, risk assessment of MENM relying solely on acute single species tests might be insufficient, and major research efforts are still needed in the area of soil communities and MENM exposure.